An Invalid Alcohol Ban: Breeds a Hotbed of Crime and Violence - Chen, Mengze; Wang, Ruizhe; Wang, Zihan (International Journal of Social Sciences and Public Administration, 2025)
Between 1920 and 1933, the United States implemented Prohibition, aiming to address social issues through legal means. However, the implementation of this policy was complex and sparked widespread controversy. Prohibition led to an increase in crime and violence, with far-reaching impacts on society, the economy, and culture. Although Prohibition improved social conditions to some extent, its negative effects far outweighed its positive value, ultimately becoming a classic lesson in American social governance history.